Deregulated Patriarchy and the New Sexual Contract: One Step Forwards and Two Steps Back - Bueskens, Petra (Journal of the Motherhood Initiative for Research and Community Involvement, 2019)
Social life has changed significantly over the last four decades. Women across the Western world have entered the workforce en masse, and, together with their partners, they have delayed (and in some cases eschewed) marriage and childbearing. Motherhood, which once seemed immutable and a natural function, is now subject to choice, including where, when, how, with whom, and if to have children. Women’s individualization is the key driver of these social changes as they have sought—both individually and collectively—to release themselves from the strictures of patriarchal family structures. But has patriarchy disappeared? It is my contention that it has not. Instead, it has become fluid as with other contemporary social structures. In the "poststructural social," patriarchy has become what I call "deregulated patriarchy." Women are not legally subordinated, as in the first age of modernity; rather women are normatively free and equal. However, this freedom is now extended to women in their caregiving capacities, and, thus, bearing and rearing children become women’s individual problem. In late modernity, motherhood has become an individualized risk, the consequences of which can be seen in women’s interrupted employment histories and drastically reduced lifetime earnings. Where divorce is normal, such individualized responsibility for children is a source of profound injustice. This situation produces a complex picture of women’s collective situation; women are free, and they are subordinated—it just depends on which phase of the life-course we are looking at. My key contention is that women are, with important intersectional differences, free as individuals and constrained as mothers, and that these two apparently polar outcomes are mutually constitutive, which generates major paradoxes in women’s civil status in contemporary Western societies.